Acute pancreatitis in 60 Iranian children: do pediatricians follow the new guidelines in diagnosis and management of acute pancreatitis? - Mahsa Soti Khiabani; Mahya Sadat Mohammadi; Seyyed Amirreza Ghoreyshi; Pejman Rohani; Hosein Alimadad; Mohammad Hassan Sohoul (BMC, 2022)
Abstract Background The incidence of acute pancreatitis in children is increasing, but causes and diagnostic and therapeutic methods are various in different centers. The aim of this study was to investigate the common causes and routine diagnostic and therapeutic methods of acute pancreatitis in children in a pediatric gastrointestinal referral center and its accordance with existing guidelines. Methods In this retrospective, cross-sectional study, a total of 60 children with a diagnosis of acute pancreatitis, were studied. Results The most common causes of acute pancreatitis were systemic and metabolic diseases and medications. CT scan was performed for 36% of patients, but 31% of patients, for whom a CT scan was performed had no clear indication of CT scan. Only half of the patients received fluid 1.5 times their maintenance in the first 24 h. Antibiotic therapy was performed for 48% of patients but medical indications for antibiotic treatment were found in only 34% of cases. During the COVID-19 pandemic, the relative incidence of acute pancreatitis was increased. Conclusions In children with systemic and metabolic disease and using anticonvulsant drugs, it is important to consider the incidence of this disease. In clinical education, the risks of radiation due to unnecessary CT scans and inappropriate prescription of antibiotics need to be emphasized. More research should be done to study the association between COVID-19 and acute pancreatitis.